Study of Generalization of Nearly Fuzzy Open Sets - Kunal Kumar Singh,; Dr. Raj Narayan Singh, (International Journal of Scientific Research in Science and Technology, 2025)
The purpose of this paper is to introduce the concepts of fuzzy C−regular open sets, fuzzy C−−open sets, fuzzy C−semi open sets and fuzzy C−pre open sets where C:[0,1][0,1]is an arbitrary complement function.
Keywords: Fuzzy Closed Set; Fuzzy Open Set; Function; Boundary; Closers